Abdominal muscle activity during breathing in different postural sets in healthy subjects - Mesquita Montes, António (2019)
This study aims to evaluate the effect of different postural sets on abdominal muscle activity during breathing in healthy subjects. Twenty-nine higher education students (20.86 ± 1.48 years; 9 males) breathed at the same rhythm (inspiration: 2 s; expiration: 4 s) in supine, standing, tripod and 4-point-kneeling positions. Surface electromyography was performed to assess the activation intensity of rectus abdominis, external oblique and transversus abdominis/internal oblique muscles during inspiration and expiration. During both breathing phases, the activation intensity of external oblique and transversus abdominis/internal oblique was significantly higher in standing when compared to supine (p ≤ 0.001). No significant differences were found between tripod position and 4-point-kneeling positions. Transversus abdominis/internal oblique activation intensity in these positions was higher than in supine and lower than in standing. Postural load and gravitational stretch are factors that should be considered in relation to the specific recruitment of abdominal muscles for breathing mechanics.